2019
DOI: 10.1021/acsami.9b05995
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Stability of Phosphate-NASICON Solid Electrolytes in Ni-Rich NCM Cathode-Based Solid-State Batteries

Abstract: A nondegrading, low-impedance interface between a solid electrolyte and cathode active materials remains a key challenge for the development of functional all-solid-state batteries (ASSBs). The widely employed thiophosphate-based solid electrolytes are not stable toward oxidation and suffer from growing interface resistance and thus rapid fading of capacity in a solid-state battery. In contrast, NASICON-type phosphates such as Li1+x Al x Ti2–x (PO4)3 and Li1+x Al x Ge2–x (PO4)3 are stable at high potentials, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 88 publications
1
63
1
Order By: Relevance
“…Of several equivalent circuits of two to four RQ elements, that with three RQ elements showed the best fitting result (Fig. 4g and Table S1, ESI †) for this study, whereas two 21,[67][68][69] or three 70,71 RQ elements have been employed for the fitting of other battery systems. Our spectra contain two small semicircles at high ((RQ) 2 ) and low frequency ((RQ) 4 ) and one larger semicircle at mid frequency ((RQ) 3 ), which all increased; however, the main degradation originated from the process at mid frequency, (RQ) 3 .…”
Section: Licoo 2 -Llzo Composite Cathodes For Ssbsmentioning
confidence: 99%
“…Of several equivalent circuits of two to four RQ elements, that with three RQ elements showed the best fitting result (Fig. 4g and Table S1, ESI †) for this study, whereas two 21,[67][68][69] or three 70,71 RQ elements have been employed for the fitting of other battery systems. Our spectra contain two small semicircles at high ((RQ) 2 ) and low frequency ((RQ) 4 ) and one larger semicircle at mid frequency ((RQ) 3 ), which all increased; however, the main degradation originated from the process at mid frequency, (RQ) 3 .…”
Section: Licoo 2 -Llzo Composite Cathodes For Ssbsmentioning
confidence: 99%
“…It is worth noting that the interphase formation is the consequence of the interplay between cathode and solid electrolyte, meaning that it not only depends on the intrinsic characteristics of electrolyte but also involves cathode. [ 89,90 ] From the first‐principles study by Miara et al, the reactivity of LiFePO 4 and LiMnO 2 against Li 7 La 3 Zr 2 O 12 was much higher than LiCoO 2 within the stability window of 3.8 V, which may be a partial explanation for low interface resistance and high capacity retention within 100 cycles of LiCoO 2 in Li 6.75 La 3 Zr 1.75 Nb 0.25 O 12 ‐based battery demonstrated by Ohta and co‐workers. [ 87,91 ] Another interface in the cathode electrode that may confront interphase formation is the carbon additive/solid electrolyte interface.…”
Section: Issues For the Cathode Encountering Solid Electrolytementioning
confidence: 99%
“…A similar interfacial product during charge was also reported when β-Li 3 PS 4 was used as one of the cathode components in other stu dies. [320,326,339,354,355] More specifically, the effect of different cut-off voltages from 4.0, 4.3, and 4.6-5.0 V on the interfacial resistance of the β-Li 3 PS 4 -NCM811 interface was investigated for a Li-In|β-Li 3 PS 4 |β-Li 3 PS 4 -NCM811 cell (Figure 9a). [320] Using electrochemical cycling experiments, electrochemical impedance spectroscopy (EIS), and ex situ/in situ XPS, significant interfacial resistance was shown to evolve, severely affecting the battery performance above charging voltages of 4.3 V. Furthermore, depth profiling of the forming interphase revealed that most of the decomposition occurred in direct contact with the current collector, explaining the local electric potential drop, [320] Copyright 2019, Royal Society of Chemistry.…”
Section: Electrochemical Oxidation and Chemical Reaction During Cyclementioning
confidence: 99%